Ether Derivatives of Naringenin and Their Oximes as Factors Modulating Bacterial Adhesion - Anna Duda-Madej; Joanna Kozłowska; Dagmara Baczyńska; Paweł Krzyżek (MDPI AG, 2023)
Because of the close connection between adhesion and many vital cellular functions, the search for new compounds modulating the adhesion of bacteria belonging to the intestinal microbiota is a great challenge and a clinical need. Based on our previous studies, we discovered that O-lkyl naringenin derivatives and their oximes exhibit antimicrobial activity against antibiotic-resistant pathogens. The current study was aimed at determining the modulatory effect of these compounds on the adhesion of selected representatives of the intestinal microbiota: Escherichia coli, a commensal representative of the intestinal microbiota, and Enterococcus faecalis, a bacterium that naturally colonizes the intestines but has disease-promoting potential. To better reflect the variety of real-life scenarios, we performed these studies using two different intestinal cell lines: the physiologically functioning ("healthy") 3T3-L1 cell line and the disease-mimicking, cancerous HT-29 line. The study was performed in vitro under static and microfluidic conditions generated by the Bioflux system. We detected the modulatory effect of the tested O-alkyl naringenin derivatives on bacterial adhesion, which was dependent on the cell line studied and was more significant for E. coli than for E. faecalis. In addition, it was noticed that this activity was affected by the concentration of the tested compound and its structure (length of the carbon chain). In summary, O-alkyl naringenin derivatives and their oximes possess a promising modulatory effect on the adhesion of selected representatives of the intestinal microbiota.